Pendeteksian Keamanan Website SMA Greenschool Menggunakan Metode Owasp dengan Pengujian XSS - Putri Charly; Kadek Erik Diatmika; I Made Panji Prayoga; I Made Edy Listartha (FORMAT, 2022)
Information security is an important thing that must be considered for every individual and agency, because if information can accessed by unauthorized people then accuracy of the information can be doubted, becoming misleading information and even various problems will be found.  Such problems can be malware attacks, exploits, or database injections. In this study, the mechanism of risk assessment methods was carried out on the website information system of greenschool high school. As the name implies XSS or stands for Cross Site Scripting is one form of interference in the form of Code Injection Attack or code injection attack. Where attackers or outsiders insert malicious code that is usually in the form of Javascript. This’s because the main purpose of using XSS is to retrieve important data and send a program that can damage the user but as if the cause is from the web itself. Web security solutions from hacker interference or attacks can be done by means of self-test, namely testing conducted on the web legally with activities such as hackers. Therefore, an analysis of the vulnerability of  system that refers to the standardization of open web application security project (OWASP) security with combination of several security tools.